Gene-based Therapeutic Tools in the Treatment of Cornea Disease - Lu, Xiao-Xiao; Zhao, Shao-Zhen (Current Gene Therapy, 2019)
Background: As one of the main blinding ocular diseases, corneal blindness resulted from neovascularization that disrupts the angiogenic privilege of corneal avascularity. Following neovascularization, inflammatory cells are infiltrating into cornea to strengthen corneal injury. How to maintain corneal angiogenic privilege to treat corneal disease has been investigated for decades. Methodology: Local administration of viral and non-viral-mediated anti-angiogenic factors reduces angiogenic protein expression in situ with limited or free of off-target effects upon gene delivery. Recently, Mesenchymal Stem Cells (MSCs) have been studied to treat corneal diseases. Once MSCs are manipulated to express certain genes of interest, they could achieve superior therapeutic efficacy after transplantation. Discussion: In the text, we first introduce the pathological development of corneal disease in the aspects of neovascularization and inflammation. We summarize how MSCs become an ideal candidate in cell therapy for treating injured cornea, focusing on cell biology, property and features. We provide an updated review of gene-based therapies in animals and preclinical studies in the aspects of controlling target gene expression, safety and efficacy. Gene transfer vectors are potent to induce candidate protein expression. Delivered by vectors, MSCs are equipped with certain characters by expressing a protein of interest, which facilitates better for MSC-mediated therapeutic intervention for the treatment of corneal disease. Conclusion: As the core of this review, we discuss how MSCs could be engineered to be vector system to achieve enhanced therapeutic efficiency after injection.
Keywords: Gene therapy